PENGARUH KARAKTERISTIK SEGMENTASI PASAR TERHADAP TINGKAT HUNIAN KAMAR THE ALEA HOTEL SEMINYAK - Dewa Gede Surya (Majalah Ilmiah Widyacakra, 2019)
The Title Research is The Influence of Market Segmentation On Room Occupancy At The Alea Hotel Seminyak. Market segmentation is basically a way to differentiate markets according to several characters from customers which are generally classified into four, namely geographical, demographical, psychographic and behavioral. By diving the market into segments will provide an illustration for the company to determine which segment will be served to be able to set up a more attractive strategy in order to maintain and increase the amount of revenue from room occupancy rate of rooms sold every day. This research aimed to analyze the influence of market segmentation on room occupancy at The Alea Hotel Seminyak. The sample of this research is 70 guests at The Alea Hotel Seminyak. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, by means of questionnaires with likert scale. The analytical technique used is simple linier regression analysis. Results of statistical analysis known that the market segmentation influenced on room occupancy is 18,7%, based on hypothesis testing with t-test results, it can be concluded that the market segmentation variable (X) partially and significantly positive influenced on room occupancy variable (Y) with value of t-test is 3,960 and sig. 0,000 at The Alea Hotel Seminyak.